The Improvement of Down Syndrome Children’s Independency Through Vocational Skill Training - Noor Rita Syofiyawati; Asrowi Asrowi; Gunarhadi Gunarhadi; Siti S Fadhilah (Journal of ICSAR, 2017)
This research aimed to find out the down syndrome children’s independency using vocational skill training. The research method employed was classroom action research (CAR). The subjects of research were four children with down syndrome. Techniques of collecting data used were a documentation study, test, and observation. The data analyzed by an interactive model by comparing prior data before and after the action through 2 cycles. The result showed that the mean score of down syndrome children independency increased. The implementation of the vocational skill training in local content subject material successfully improved the down syndrome independency.